Analisis Minat Masyarakat Berinvestasi Emas Melalui Produk Pembiayaan Cicil Emas di Bank Syariah Indonesia Menggunakan Pendekatan Theory of Planned Behavior - Afifah Afifah; Farid Ardyansyah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to determine the effect of the Theory of Planned Behavior (TPB) component and two other variables, namely investment and religious knowledge on people's interest in investing through Sharia Bank of Indonesia installment financing at the Sharia Bank of Indonesia Surabaya Diponegoro. Sub-Branch Office, the analytical method used in this analysis is quantitative analysis, the analysis used includes: validity and reliability test, classic assumption test, multiple linear regression analysis and hypothesis testing, the sample used in this study is 100 respondents, data processing is done using SPSS software 25. Research results This shows that investment attitudes have a significant effect on investment intention, with a significance value of 0.037 <0.05 and religiosity also has a significant effect on investment interest with a significance value of 0.012 <0.05. Meanwhile, the variable perception of behavioral control, subjective norm, and investment knowledge has no significant effect on investment interest as evidenced by a significant value greater than 0.05. Keywords: Community Interest, Golden Installments, TPB.